Protein purification by affinity chromatography with peptide ligands selected from the screening of combinatorial libraries - Camperi, Silvia Andrea (2010)
Affinity chromatography is likely to play an everincreasing important role in protein purification as it is the most effective method for the direct isolation and purification of biomolecules from complex mixtures. Successful separation by affinity chromatography requires the availability of a selective ligand. Short peptides are excellent ligands for affinity separations as they have higher selectivity than dyes and metals, they are more stable than antibodies to elution and cleaning conditions, and they are not likely to cause an immune response in case of leakage into the product. Furthermore, the combinatorial synthesis of peptide libraries allows obtaining millions of peptides, thus greatly facilitating the discovery of suitable affinity ligands for any given protein of interest. After screening of the library the peptides with affinity for the target protein can be identified, typically by Edman microsequencing or mass spectrometry in the case of synthetic libraries, or by DNA sequencing in the case of biological libraries. Numerous proteins have been purified in only one step with chromatographic matrices made of peptide-ligands selected from the screening of combinatorial libraries, attached to different supports.